Braveheart - Gibson, Mel; Ladd, Alan, 1937-; Davey, Bruce; Wallace, Randall; Marceau, Sophie, 1966-; McGoohan, Patrick, 1928-2009 (Widescreen DVD collection, 2006)
William Wallace is a bold Scotsman who used the steel of his blade and the fire of his intellect to rally his countrymen to liberation.